Development of a Novel 3D Bioprinted In Vitro Nano Bone Model for Breast Cancer Bone Metastasis Study. Issue 1724 (19th December 2014) - Holmes, Benjamin; Zhu, Wei; Zhang, Lijie Grace
ABSTRACT: Breast cancer (BrCa) is the second commonest cause of cancer-related deaths in women. The metastatic breast cancer exhibits a high affinity to bone, leading to debilitating skeletal complications associated with significant morbidity and poor prognosis. Traditional in vitro and in vivo BrCa bone metastasis models contain many inherent limitations with regards to controllability, reproducibility, and flexibility of design. Thus, the objective of this research is to use a 3D bioprinting system and nanomaterials to recreate a biomimetic and tunable bone model suitable for the effective simulation and study of metastatic BrCa invading and colonizing a bone environment. For this purpose, we designed and 3D printed a series of scaffolds, comprised of a bone microstructure and nano hydroxyapatites (nHA, inorganic nano components in bone). The size and geometry of the bone microstructure was varied with 250 and 150 µm pores, in repeating square and hexagon patterns, for a total of four different pore geometries. 3D bioprinted scaffolds were subsequently conjugated with nHA, using an acetylation chemical functionalization process and then characterized by scanning electron microscope (SEM). SEM imaging showed that our designed microfeatures were printable with the predesigned resolutions described above. Imaging further confirmed that acetylation effectively attached nHA to the surface of scaffolds and induced a nanoroughness. Metastatic BrCa cell 4 h adhesion and 1, 3 and 5 day proliferation were investigated in the bone model in vitro. The cell adhesion and proliferation results showed that all scaffolds are cytocompatible for BrCa cell growth; in particular the nHA scaffolds with small hexagonal pores had the highest cell density. Given this data, it can be stipulated that our 3D printed nHA scaffolds may make effective biomimetic environments for studying BrCa bone metastasis.